Uji Viabilitas Sprema Pria Pasangan Ingin Anak 3 Macam Medium - Erma Mexcorry; Anna Maria D (Jurnal Kedokteran Meditek, 2004)
Technology  of reproduction is very beneficial for infertile couples or persons with reproductive organ problem. Test of motility and viability sperms by using three mediums in order to determine the best medium for insemination process is one aspect of in vitro fertilization process. Sperm specimens analyzed using WHO criteria. Sperms used were sperms of normospermia criteria. Test were divided into 3 groups based on medium , that is group I : BWW + BSA, group II : BWW + calf serum , group III : BWW + white egg;  examination were done step by step , BWW + BSA (1 hour): then BWW + white egg. Sperms were observed and compared with SST results in some test medium group.                 Stistical result by using correlation of Speamen ‘S shows there is no significant differences between medium BSA 10% : CS 10 % : white egg 1%, and between BSA 20 % : cs 20 % : white egg 20% and also between BSA 30%  : CS 30 % : white egg 30%